Financing alternatives and profitability of firm performance - Khoo, Jia Xin. (Universiti Malaysia Sarawak (UNIMAS), 2014)
This study is conducted to determine the financial alternatives and profitability of firm performance between the selected public listed companies in Sarawak using ordinary least square (OLS) regression method and descriptive statistics. Data is collected from companys’ website and annual report in Main Board of Bursa Malaysia website for three years period. Ordinary least square (OLS) regression method and descriptive statistics are used as method to calculate financial performance of companies. Findings show that though the companies may have adopted different approaches to structure their capital however the results have shown debt financing is more meaningful amongst the 12 Sarawak public listed companies.